State of Harmonic Compensation Technology and Its Development - LUO An; WU Chuanping; PENG Shuangjian (Kongzhi Yu Xinxi Jishu)
The classical harmonic suppression technologies are described from the two aspects of active harmonic suppression and passive harmonic suppression. Some main harmonic detection and harmonic control methods are analyzed and compared. Then the new technologies of harmonic suppression are discussed. Finally, the development trends of harmonic suppression technologies are stated.